VOLTAMMETRY UNDER HIGH-MASS TRANSPORT CONDITIONS - A HIGH-SPEED CHANNEL ELECTRODE FOR THE STUDY OF ULTRAFAST KINETICS - Rees, N; Dryfe, R; Cooper, J; Coles, B; Compton, R; Davies, S; Mccarthy, T (1995)
The design, construction, and application of a miniature channel electrode operating with very high flow conditions, of up to ca. 10 cm3 s-1, are reported. The channel cell has approximate cross-section dimensions of 0.2 cm × 100 μm so that the axial velocity of the solution through the channel can reach values as high as 75 m s-1 (270 km h-1, 167 mi h-1) at the channel center. The electrode takes the form of a microband electrode presently of length ca. 5-10 μm. With this arrangement voltammetry can be performed under flow conditions where the mass transport coefficient approaches 1.0 cm s-1. Voltammetric measurements utilizing the new cell are reported, and the mass transport is shown to be quantitatively consistent with a model in which the dominant transport is by diffusion normal to the electrode and by convection axially through the cell. Axial diffusion effects are relatively insignificant. The cell is applied to the study of ECE processes, and it is shown that homogeneous rate constants as high as 105 s-1 are readily measureable from steady-state experiments. © 1995 American Chemical Society.